Contemporary Entrepreneurship 2016
DOI: 10.1007/978-3-319-28134-6_3
|View full text |Cite
|
Sign up to set email alerts
|

Linking Entrepreneurship and Economic Growth in Sweden, 1850–2000

Abstract: Entrepreneurship has gained increasing support from governments in recent decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Let us remember that ignoring asymmetry when it is present might produce erroneous inferences in hypothesis testing. Only a few studies have studied the possibility of a nonlinear relationship in country-specific analyses -see Parker et al (2012) for the UK, Congregado et al (2012) for Spain and the US and Box et al (2014) for Sweden. However, to the best of our knowledge, no cross-country studies that account for nonlinearity exist at the present time.…”
Section: End Of Tablementioning
confidence: 99%
“…Let us remember that ignoring asymmetry when it is present might produce erroneous inferences in hypothesis testing. Only a few studies have studied the possibility of a nonlinear relationship in country-specific analyses -see Parker et al (2012) for the UK, Congregado et al (2012) for Spain and the US and Box et al (2014) for Sweden. However, to the best of our knowledge, no cross-country studies that account for nonlinearity exist at the present time.…”
Section: End Of Tablementioning
confidence: 99%
“…H2 proposes that entrepreneurship has a positive effect on economic growth. In this regard, there is extensive literature analyzing the link between both variables [17,[61][62][63][64][65][66][67][68]. Indeed, many previous studies have affirmed a clear positive relationship between entrepreneurship for the case of self-employment as a proxy and economic growth [69][70][71][72].…”
Section: Empirical Analysis and Resultsmentioning
confidence: 99%
“…Global Entrepreneurship Monitor (GEM) has suggested 12 different variables to justify the performance of the entrepreneurship ecosystem across countries. Hence, earlier researchers [ [31] , [32] , [33] , [34] , [35] ] used different variables such as self-employment or business ownership rate, employment rate, number of company formations, self-employment rate, entry employment, new establishments firms, new business registration, business ownership rate, self-employment rate, total entrepreneurial activity rate to justify the entrepreneurship ecosystem's performance. A study reported that business ownership rate has a U-shaped relationship with economic development across countries [ 31 ].…”
Section: Review Of Literaturementioning
confidence: 99%
“…In Ref. [ 33 ] authors have studied a positive impact of entrepreneurship ecosystem on economic development in Sweden. The total entrepreneurial activity rate can be used to express the position of entrepreneurship ecosystem [ 34 ].…”
Section: Review Of Literaturementioning
confidence: 99%